2007
DOI: 10.1073/pnas.0701699104
|View full text |Cite
|
Sign up to set email alerts
|

Reorientional dynamics of water molecules in anionic hydration shells

Abstract: Water molecule rotational dynamics within a chloride anion's first hydration shell are investigated through simulations. In contrast to recent suggestions that the ion's hydration shell is rigid during a water's reorientation, we find a labile hydration sphere, consistent with previous assessments of chloride as a weak structure breaker. The nondiffusive reorientation mechanism found involves a hydrogen-bond partner switch with a large amplitude angular jump and the water's departure from the anion's shell. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
351
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(387 citation statements)
references
References 36 publications
30
351
4
1
Order By: Relevance
“…The correlation times apparent from the 2D spectra and the mixed quantum-classical derived frequency calculations are well below the picosecond HB lifetimes reported here and in the literature, 14,22 i.e., we are able to discern sub-100 fs structural fluctuations from slower hydrogen bond exchange dynamics. Owing to the short vibrational lifetimes of 300 fs, these exchange processes do not contribute significantly to the observed 2D line shapes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The correlation times apparent from the 2D spectra and the mixed quantum-classical derived frequency calculations are well below the picosecond HB lifetimes reported here and in the literature, 14,22 i.e., we are able to discern sub-100 fs structural fluctuations from slower hydrogen bond exchange dynamics. Owing to the short vibrational lifetimes of 300 fs, these exchange processes do not contribute significantly to the observed 2D line shapes.…”
Section: Discussionmentioning
confidence: 66%
“…The mean HB lifetime has values of 1-2 ps in the bulk, limited by HB exchange events within 100 fs. 10,22 The role of ions in accelerating or retarding water dynamics has been discussed controversially. 23 2D IR spectra of water vibrations are spatially unselective, i.e., contain both hydration shell and bulk contributions.…”
Section: Introductionmentioning
confidence: 99%
“…From the measurement of l, it is not possible to independently determine j and j . It has been found from MD simulations of an aqueous 1 M NaCl solution that the jump angles of water molecules are 63°and 70°for switching their hydrogen bond partners from water to water and from Cl Ϫ to water, respectively (12,43). For j ϭ 63°, l ϭ 1.17 j , and for j ϭ 70°, l ϭ 1.03 j .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Laage and Hynes (12,43) have shown that the orientational relaxation of water molecules in pure water and ionic solutions is described by a jump reorientation model rather than Gaussian orientational diffusion. This model was recently applied to nanoscopic water in Nafion fuel cell membranes (19).…”
Section: Resultsmentioning
confidence: 99%
“…However, ultrafast infrared pump-probe studies and their theoretical analysis have come to the surprising conclusion that the diffusive orientational relaxation of water outside the first solvation shell of the ions is hardly affected by the presence of salts. 3,10 This has been shown in aqueous solutions of Mg(ClO 4 ) 2 , NaClO 4 , and Na 2 SO 4 . 3 In all of these cases, infrared pump-probe experiments measure a 2.5 ps decay time for the orientational relaxation of water molecules in bulk water as distinct from water molecules in the relatively stable hydration shells surrounding the cations.…”
mentioning
confidence: 99%